HOXA GENE EXPRESSION IMPLICATED IN TREATMENT RESISTANCE AND POOR PROGNOSIS IN GLIOBLASTOMA - Seidu, Naomi; Poluyi, Edward; Ikwuegbuenyi, Chibuikem; Morgan, Eghosa (MNJ (Malang Neurology Journal), 2020)
This review brings into view the prognosis attributable to glioblastoma (GBM) and resistance to treatment, surgical interventions and chemotherapy seem ineffective at procuring a better prognosis for patients with the disease. Albeit there exist varying interventions for GBM, the median survival still comes to 12 to 15 months for afflicted patients, this has aroused the need for improvement in treatment success The principal goal is to create a better prognosis and have a decline in treatment resistance invariably leading to better survival rates via adequate treatment for GBM. A relationship exists between HOX genes (homeobox genes) and glioblastoma as is evident from literature. Treatment resistance has been observed in overexpression of HOX genes, the effectiveness of treatment could result from silencing these genes A series of studies have highlighted the role that HOX genes play in glioblastoma prognosis. Promotion of human glioblastoma initiation, aggressiveness, and resistance to Temozolomide has been associated with HOXA9 as shown by Pojo et al. The role of HOX gene expression in cancer stem cells should be studied as it could provide a means of designing CSC-targeted therapies, as CSCs play a part in initiation and progression of solid tumors.